Federalism and Fiscal Transfers in India - Rangarajan, C.; Srivastava, D. K. (New York : Oxford University Press, 2024)
India's Constitution provides for a federal framework encompassing the central, state, and local governments. The system of fiscal transfers has been guided by India's Finance Commissions to bring revenues closer to expenditures across different tiers of government. In India, fifteen Finance Commissions have submitted their recommendations so far; the Sixteenth Finance Commission, which has recently been set up, is presently deliberating on issues of fiscal transfers as per constitutional provisions. Federalism and Fiscal Transfers in India provides a critical overview of the theoretical foundations guiding fiscal transfers in India and the country's empirical realities. It extensively covers not only the vertical and horizontal dimensions of fiscal transfers in the past but also looks at the contemporary issues and tensions that prevail between central and state governments, emphasising the principle and role of the Equalization Approach for determining inter-state sharing of resources. The second edition provides an updated review of the recommendations of the three most recent Finance Commissions, namely, the Thirteenth, Fourteenth, and Fifteenth Commissions. It also comments on the salient issues facing the Sixteenth Finance Commission and the long-term reforms needed for an equitable, stable, and efficient system of fiscal transfers in India.
Keywords: Federal government -- India; India -- Economic policy -- Politics and government; Intergovernmental fiscal relations -- India